Cortejo y cópula en la broca de la semilla de guanábana Bephratelloides pomorum (Hymenoptera: Eurytomidae) - B. Pereira, Mónica J (Universidad de Costa Rica, 1998)
Adults of soursop seed borer Bephratelloides pOlllorum (Hymenoplera: Eurytomidae) were collected from fruits in Maceió, State of Alagoas, Brazil. The courtship and copulatíon behaviours of B. pomorum were described under 27.6 ± O.loC, R.H. of 77 .50 ± 0.8%. A virgin couple of B. pomorum was placed daily in a glass cage for observing lhe courtship and coplllation behaviour during a period of 12 days. This procedllre was repealed ten times by using grollps of 10 to 12 virgin couples per replicate. The observations fol' each replicate wel'e ended after lhe first copulation. In general, males emerged first and newly emerged females elicited male courtship and mating behaviours. The behavioural patterns of males consisted of well-defined sequences such as approaching to female, wing fanning, regulatory body movements, copulation. rubbing aedeago on female abdome, antennae and mOllthparts grooming